Effect of Laser Acupuncture Shoot on Ova Point of Male Mojosari Duck (Anas plathyrhynchos) on The Number of Sertoli and Leydig Cells - Adikara, Yuanara AR; Samik, Abdul; Yudaniayanti, Ira S; Adikara, Tatang S; Hestianah, Eka P; Utama, Suzanita (KnE Life Sciences, 2017)
Demand for duck eggs and meat recently increased along with the increasing interest of the community to consume duck eggs and meat. Due to that reason researcher try to find the best way to enhance the reproductive ability of livestock., which is in this research by laser puncture shot. Eighteen ducks were allocated into three groups, the control group, the first treatment group with laserpuncture shoot dose of 0.2 Joule (J), and the second treatment group with laser puncture shoot dose of 0.4 J. Data were analyzed with ANOVA and further tested by Duncan multiple range test. Research result showed that laser puncture shoot with a dose of 0.2 J and 0.4 J decreased the number of Sertoli and Leydig cells. Keywords: Mojosari duck; laser acupuncture; Sertoli cells; Leydig cells